Investigasi Atas Perilaku Konsumen Musik Indonesia Dalam Menggunakan Produk Musik Bajakan - Sony Kusumasondjaja; Nazar Karami (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2013)
The increasing adoption of pirated music products intesifies the needs to understand factors influecing consumers to buy pirated music products. This study examines the impact of attribute satisfaction, singer idolization, prosecution risk, social consensus, maginitude of consequences, and proximity on consumer attitude toward pirated music products and their intention to buy the products. Data was collected through online survey distributed on Facebook involving pirated music product consumers. Findings suggest that attribute satisfaction, maginitude of consequences, and proximity affect attitude toward the pirated music products, while attribute satisfaction, prosecution risk, social consensus, and maginitude of consequences influence consumer intention to buy pirated products. Research contributions and implications are discussed.